New strategy for renal fibrosis: Targeting Smad3 proteins for ubiquitination and degradation - Wang, Xin; Feng, Shaozhen; Fan, Jinjin; Li, Xiaoyan; Wen, Qiong; Luo, Ning (Biochemical pharmacology, 2016)
[Display omitted] Smad3 is a critical signaling protein in renal fibrosis. Proteolysis targeting chimeric molecules (PROTACs) are small molecules designed to degrade target proteins via ubiquitination. They have three components: (1) a recognition motif for E3 ligase; (2) a linker; and (3) a ligand for the target protein. We aimed to design a new PROTAC to prevent renal fibrosis by targeting Smad3 proteins and using hydroxylated pentapeptide of hypoxia-inducible factor-1α as the recognition motif for von Hippel–Lindau (VHL) ubiquitin ligase (E3). Computer-aided drug design was used to find a specific ligand targeting Smad3. Surface plasmon resonance (SPR) was used to verify and optimize screening results. Synthesized PROTAC was validated by two-stage mass spectrometry. The PROTAC’s specificity for VHL (E3 ligase) was proved with two human renal carcinoma cell lines, 786-0 (VHL−) and ACHN (VHL+), and its anti-fibrosis effect was tested in renal fibrosis cell models. Thirteen small molecular compounds (SMCs) were obtained from the Enamine library using GLIDE molecular docking program. SPR results showed that #8 SMC (EN300-72284) combined best with Smad3 (KD=4.547×10−5M). Mass spectrometry showed that synthesized PROTAC had the correct peptide molecular weights. Western blot showed Smad3 was degraded by PROTAC with whole-cell lysate of ACHN but not 786-0. Degradation, but not ubiquitination, of Smad3 was inhibited by proteasome inhibitor MG132. The upregulation of fibronectin and Collagen I induced by TGF-β1 in both renal fibroblast and mesangial cells were inhibited by PROTAC. The new PROTAC might prevent renal fibrosis by targeting Smad3 for ubiquitination and degradation.